Targeted Decomplexation of Metal Complexes for Efficient Metal Recovery by Ozone/Percarbonate - Ying Chen; Mu, Yi; Lei Tian; Ling-Ling Zheng; Mei, Yi; Xing, Qiu-Ju; Liu, Wen; Jian-Ping Zou; Yang, Lixia; Luo, Shenglian; Wu, Daishe (Environmental Science & Technology, 2023)
Traditional methods cannot efficiently recover Cu from Cu(II)–EDTA wastewater and encounter the formation of secondary contaminants. In this study, an ozone/percarbonate (O3/SPC) process was proposed to efficiently decomplex Cu(II)–EDTA and simultaneously recover Cu. The results demonstrate that the O3/SPC process achieves 100% recovery of Cu with the corresponding kobs value of 0.103 min–1 compared with the typical •OH-based O3/H2O2 process (81.2%, 0.042 min–1). The carbonate radical anion (CO3•–) is generated from the O3/SPC process and carries out the targeted attack of amino groups of Cu(II)–EDTA for decarboxylation and deamination processes, resulting in successive cleavage of Cu–O and Cu–N bonds. In comparison, the •OH-based O3/H2O2 process is predominantly responsible for the breakage of Cu–O bonds via decarboxylation and formic acid removal. Moreover, the released Cu(II) can be transformed into stable copper precipitates by employing an endogenous precipitant (CO32–), accompanied by toxic-free byproducts in the O3/SPC process. More importantly, the O3/SPC process exhibits excellent metal recovery in the treatment of real copper electroplating wastewater and other metal–EDTA complexes. This study provides a promising technology and opens a new avenue for the efficient decomplexation of metal–organic complexes with simultaneous recovery of valuable metal resources.